A new approach to treatment of acute heart failure. Issue 5 (May 2016) - Goldsmith, Steven R.
Abstract: Conventional therapies for acute decongestion have yielded uniformly poor results in patients with acute heart failure (AHF). The failure of current strategies may be due to advanced disease in hospitalized patients, incomplete therapy, inherent limitations to existing therapy, or some combination of all three factors. Loop diuretics are the mainstay of current therapy and are in theory not ideal since while producing immediate intravascular volume reduction and relief of symptoms they activate neurohormonal forces that are deleterious to both the heart and the kidney. Ultrafiltration is an alternative to loop diuretics but has not proved advantageous in the setting of renal dysfunction, and if not carefully applied may also aggravate neurohormonal imbalance. In theory decongestive therapy for AHF should remove large volumes of fluid quickly and safely and improve symptoms, particularly dyspnea, without aggravating renal dysfunction or causing neurohormonal activation. Several studies have now suggested that the use of aquaretics such as antagonists to the V2 receptor for arginine vasopressin may be useful as adjunctive therapy in AHF, particularly when renal dysfunction and/or hyponatremia are present. These agents leverage osmotic forces to produce tissue decongestion while causing a water diuresis. They do not adversely affect renal function or neurohormonal balance. Building on the current base of knowledge about outcomes in AHF together with the only study of vasopressin antagonists as short-term monotherapy in chronic heart failure, it would be reasonable to design a trial in AHF in which the use of loop diuretics was minimized in favor of these agents.